Music Therapy for Reducing Pain Intensity in Post-Laparotomy Patients: A Quasi-Experimental Study in Indonesia - St. Nurfatul Jannah; Wiwiek Hidayati Jaya; Anester B Lololuan (An Idea Health Journal, 2026)
Postoperative pain following laparotomy remains a significant challenge, with 58-60% of patients experiencing moderate to severe pain despite standard pharmacological management. Music therapy has emerged as a promising non-pharmacological intervention. This study aimed to examine the effectiveness of music therapy in reducing pain intensity among patients following laparotomy surgery. A quasi-experimental one-group pretest-posttest design was conducted at RSUD Daya Kota Makassar, Indonesia, from April 1 to April 30, 2025. A total of 34 post-laparotomy patients were recruited using total sampling. Inclusion criteria were adults aged ≥18 years on postoperative day 1, literate, able to communicate in Indonesian, and willing to participate. Exclusion criteria included severe pain (NRS 7-10), recent analgesic use (<2 hours), or continuous analgesic administration. Participants received classical music therapy via headphones for 10-20 minutes daily over three consecutive days. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after the intervention. The mean pain intensity decreased significantly from 4.76 ± 1.18 at baseline to 2.29 ± 0.87 post-intervention (Z = -5.188, p .000), representing a mean reduction of 2.47 points. The distribution of pain categories shifted substantially, with mild pain increasing from 20.6% to 88.2%, while moderate pain decreased from 79.4% to 11.8% following the intervention. The significant reduction in pain scores supports the integration of music therapy as a safe, accessible, and cost-effective complementary approach to standard postoperative pain management protocols in clinical practice.